2013
DOI: 10.3855/jidc.3154
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evaluation of drug resistance in clinical isolates of Salmonella enterica serovar Typhi from Pakistan

Abstract: Introduction: This study aimed to determine the drug susceptibility patterns and genetic elements related to drug resistance in isolates of Salmonella enterica serovar Typhi (S. Typhi) from the Faisalabad region of Pakistan. Methodology: The drug resistance status of 80 isolates were evaluated by determining antimicrobial susceptibility, MICs, drug resistance genes involved, and the presence of integrons. Nalidixic acid resistance and reduced susceptibility to ciprofloxacin were also investigated by mutation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 59 publications
1
19
1
Order By: Relevance
“…One study reported 6% (16 isolates) ceftriaxone resistance using microdilution testing [86]. The remaining 21 studies performed Kirby-Bauer disc diffusion testing; of those, only three studies, one with 43% (80 isolates) [87], one with 15% (630 isolates) [46] and one with 11% (300 isolates) resistance [88], determined ceftriaxone MICs. However, ceftriaxone resistance was not confirmed by MIC testing (agar dilution) in the two latter studies [46, 88].…”
Section: Resultsmentioning
confidence: 99%
“…One study reported 6% (16 isolates) ceftriaxone resistance using microdilution testing [86]. The remaining 21 studies performed Kirby-Bauer disc diffusion testing; of those, only three studies, one with 43% (80 isolates) [87], one with 15% (630 isolates) [46] and one with 11% (300 isolates) resistance [88], determined ceftriaxone MICs. However, ceftriaxone resistance was not confirmed by MIC testing (agar dilution) in the two latter studies [46, 88].…”
Section: Resultsmentioning
confidence: 99%
“…Typhi resistance to ceftriaxone has been documented as emerging in Bangladesh and Kuwait for up to 15 years (Afzal et al, 2013). Indeed, a recent study in Pakistan and India concludes that 73.7% (n=80), 56.2%, and 52.5% of bacterial isolates had developed resistance to sulfonamide, ampicillin, or streptomycin, respectively (Afzal et al, 2013), with 58.7% of the overall isolates having multi-drug resistance. Resistant strains have also been observed in Kenya with resistance against cotrimoxazole in 66.7% (22 individuals) of the S .…”
Section: Introductionmentioning
confidence: 99%
“…3 With this burden, treating typhoid fever is huge challenge for health care provider in developing countries. Factors like nonspecific signs and symptoms 4 , variable yield of organism on blood culture 5 and finally drug resistance 6 are one by one increasing the complexity of managing this disease. Over the past three decades drug susceptibility against Salmonella Typhi and Paratyphi has been changed significantly.…”
Section: Introductionmentioning
confidence: 99%